Polymerase Chain Reaction-And Rna Hybridization-Based Method for the Investigation of Deep-Seated Candidiasis - Peter R Couroux; Zafar Hussain; Frank Rutledge; Robert Lannigan; Edward D Ralph; Barbara Nancekivell; Thomas W Austin (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the usefulness of a polymerase chain reaction (PCR) and RNA hybridization method for the diagnosis of invasive candidiasis and to compare its sensitivity with blood cultures.